The Impact of Product Innovation and Service Quality on Customer Loyalty (Literature Review) - Sitika Asri Mahyani; Liansi Hartini; Dela Restu Puspita; Agil Dwi Ronaldo; Hanlee Canghi Soulamsa; Ririn Harini (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the influence of product innovation and service quality on customer loyalty through a literature review approach. Increasingly fierce business competition demands that companies continuously innovate and provide quality service to maintain customer loyalty. The research method used was a qualitative approach with a literature review. This approach involved examining various scientific journals, books, articles, and previous research relevant to product innovation, service quality, and customer loyalty. The results of the study indicate that product innovation has a positive effect on customer loyalty because innovative products can provide added value, attract consumer interest, and meet customer needs in line with market developments. Furthermore, service quality also has a significant influence on customer loyalty by creating customer satisfaction, trust, and comfort in using a product or service. Good service can foster a positive relationship between a company and its customers, thereby increasing repeat purchases and customer commitment to the company. Furthermore, the combination of product innovation and service quality can increase customer loyalty optimally and sustainably. Therefore, companies need to continuously develop innovative products and improve service quality to maintain competitiveness and foster long-term customer loyalty.